Faculty’s lived experiences in recognizing nursing students’ psychological support needs in Saudi Arabia - Samirh Said Alqhtani; Seham Alselami; Hend Alnajjar (BMC Medical Education)
Abstract Background/Objectives Nursing students often experience high levels of stress, anxiety, and depression throughout their academic and clinical education. Academic and social pressures can intensify mental health challenges during university studies. Faculty members play a vital role in fostering a supportive and inclusive learning environment that prioritizes the mental well-being of nursing students. This study aimed to gain a deeper understanding of faculty members’ experience in recognizing nursing students’ psychological support needs. Methods This qualitative study involved purposive sampling of faculty members in two nursing colleges in Saudi Arabia. In-depth, face-to-face, semi-structured interviews were conducted with eight faculty members using open-ended questions. The interviews were recorded, transcribed verbatim, and thematically analyzed using the NVivo program. Results Data analysis revealed four major themes: students’ emotional support, challenges of supporting students, recognition of distress and utilizing resources, and faculty training needs. Conclusions This study identified a multidimensional role of faculty members in supporting students’ emotional well-being and academic success. However, they faced challenges that need to be addressed through educational organizations. There is a need to examine the effectiveness of training programs in educating faculty on identifying mental health issues and providing adequate support.